Kombinasi Serat Batang Aren dan Pasir Merapi pada Hidroponik Substrat Kailan - Anik Fitri Astuti; Dwi Hardjoko; Muji Rahayu (Universitas Sebelas Maret, 2016)
Kailan is a horticultural commodity that interest but productivity of kailan reduce caused by the cultivation of agricultural land which is getting slightly. Need effort to increase productivity of kailan by applying hydroponic substrate. This study uses merapi sand and arenga wood fiber as a hydroponic substrate medium. Merapi sand is easily porous. Arenga wood fiber is waste produced by palm industry which not used maximum. This study purpose to assess whether the treatment of a mixture of merapi sand and arenga wood fiber with hydroponic substrate systems affect kailan’s growth and product. The method used completely randomized design with one factor consists of 1 control and 13 treatments. The results showed that mixture of merapi sand and arenga wood fiber give different effect on variable. Mixture of 25% arenga wood fiber and 75% Merapi sand (1: 3) have inclined more great value in the roots fresh weight and plant fresh weight. Merapi sand 100% give inclined more great value in the variable plant height and amount of leaves.